Meningkatkan Kreatifitas Siswa melalui STEM dalam Pembelajaran IPA Increasing Student Creativity through STEM in Science Learning - Rikardus Herak; Godelfridus Hadung Lamanepa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2019)
This study aims to improve students' creativity through STEM in Science Learning in Class VIII SMP Negeri 11Kupang. The STEM approach is associated with the environment, so that a learning is realized that presents the real world experienced by students in everyday life. This means that through the STEM approach students are not just memorizing concepts, but rather how students understand and understand scientific concepts and their relationships in everyday life. The problem in this study is the low creativity of students in science learning. The subjects of this study were class VIII J students totaling 25 people. This type of research is classroom action research (CAR). This research model is in the form of a cycle consisting of four stages, namely: planning, action, observation and reflection. Data collection techniques in the form of observation sheets and questionnaires. The analysis technique uses descriptive analysis. The results of the study show that science learning with the STEM approach can train students 'creative abilities in linking the four fields of the exact science so that they have deep insights and can enhance students' creativity Keywords: Creativity, STEM, Learning outcomes